The Practice of Disclosing Human Capital in Bank Jawa Barat and Banten: From the Perspective of Political Economy of Accounting - Puspitasari, Ayu B1034141002 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
The purpose of this research is to know the practice of HCD in Bank BJB’s annual reports from the perspective of PEA and to know the reasons for or motivations behind disclosure of HC in Bank BJB’s annual report from the perspective of PEA. Nine years annual reports (2008 – 2016) of Bank BJB are analyzed in qualitative manner by employing content analysis method. Findings reveal that HCD in Bank BJB’s annual reports have economic, social, and political aspects. It is a way to reduce tension among stakeholders and information asymmetry. Besides, motivations behind HCD are various. However, in general, it is because HC is an important asset for company to achieve its vision. HC is used to create value for company, sustain, and legitimize its existence. Therefore, findings correspond with theory of PEA which state that HCD is a mean to create, sustain, and legitimize activities in the private interest of the firm.Keywords: human capital, disclosure, political economy of accounting